Strategy for Using Social Media As A Means of Digital Business Promotion for UMKM Bolu Al-Rindu Ringinanom Kidney Kediri City - Al-Bahri, Imam Fathulloh; Renata, Felicia; Aprillia, Dita Damayanti; Sajidha, Anggun; Fitriyana, Wahyu Tia; Makmun, M. Sukron; Buana, Anom Surya; Muzaki, M. Afan; Lestariningrum, Anik (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
In the era of digital technology development, technological developments in the form of social media are not only large companies experiencing the benefits, but Micro, Small, and Medium Enterprises (MSMEs) can also take advantage of these advances to reach global markets and increase operational efficiency. Although social media has become a very popular tool for promoting products and services to potential consumers, many MSMEs face serious challenges due to a lack of technological knowledge and skills, as well as immature digital infrastructure. This challenge is especially felt at the local level, as experienced by the MSMEs of Bolu AL-RINDU, where many entrepreneurs are not yet fully connected to social media and digital platforms. To overcome this problem, this research aims to increase the use of social media, especially the TikTok platform, by Bolu AL-RINDU MSMEs. Through a qualitative approach, with data collection, observation, and documentation, this research will analyze the effectiveness of social media in MSME marketing and sales strategies.